The New Way Improve Learners' Speaking Skills: Picture and Picture Learning Media Based on Articulate Storyline - Yolanda, Stefi; Winarni, Retno; Yulisetiani, Septi (Journal of Education Technology, 2022)
Success in the learning process in elementary schools can be seen from the active participation of students in conveying their ideas and feelings through good speaking skills. The low speaking ability of students in elementary schools hurts the quality of learning. Therefore, learning media is needed to improve students' speaking skills, using interactive picture and picture learning media based on storyline articulation. This study aims to create learning media that can improve the speaking skills of elementary school students. This research is a research and development (RnD) with the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects of this study were teachers and students of grade 3 elementary school. Data collection techniques were carried out using documentation, interviews, and questionnaires. The data analysis technique used is descriptive qualitative analysis technique and quantitative analysis. The results of the study obtained valid, practical. Effective learning media with an excellent validity level, namely 92% and 90.90% for materials and media, the practicality level of students and teachers was 82.5%; 85% and 82.5%; 90% with a convenient category and has an effect that can be seen from the Z count of -3.411 with Asymp. Sig 0.001 of 12 and 15 students from the limited group and the broad group who took the test and had a pretest average of 68.4 and got a post-test average of 83.4. Thus, this media can improve the speaking skills of elementary school children.